2010
DOI: 10.3310/hta14210
|View full text |Cite
|
Sign up to set email alerts
|

Early referral strategies for management of people with markers of renal disease: a systematic review of the evidence of clinical effectiveness, cost-effectiveness and economic analysis

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
144
0
13

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(159 citation statements)
references
References 177 publications
(607 reference statements)
2
144
0
13
Order By: Relevance
“…Guidelines for vascular access placement (13) might have created unintended consequences; after the access is ready for use, providers may have lower thresholds for initiating dialysis. Many retrospective cohort studies have suggested a survival benefit during the first 1 year of dialysis for patients who receive predialysis nephrology care and patients who initiate dialysis with an arteriovenous fistula or graft (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Analyses that evaluate the influence of predialysis nephrology care and dialysis access at initiation on outcomes may suffer from lead time bias; nephrologists may accelerate dialysis start dates for well-prepared patients under their care, and survival analyses that begin with dialysis initiation may show better survival in well-prepared patients.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines for vascular access placement (13) might have created unintended consequences; after the access is ready for use, providers may have lower thresholds for initiating dialysis. Many retrospective cohort studies have suggested a survival benefit during the first 1 year of dialysis for patients who receive predialysis nephrology care and patients who initiate dialysis with an arteriovenous fistula or graft (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Analyses that evaluate the influence of predialysis nephrology care and dialysis access at initiation on outcomes may suffer from lead time bias; nephrologists may accelerate dialysis start dates for well-prepared patients under their care, and survival analyses that begin with dialysis initiation may show better survival in well-prepared patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to clinical underutilization, there is also uncertainty with respect to whether there are additional costs or savings when implementing early intervention programs (11)(12)(13)(14). One study looked at stage 4 CKD patients who were under the care of a nephrologist (12), but this study involved later stage CKD with creatinine clearance of 20 ml/min or lower.…”
Section: Introductionmentioning
confidence: 99%
“…A different cost-effectiveness analysis that included patients over 50 years of age with proteinuria indicated that early screening was cost-effective for ages 60 and over or cases with hypertension and not diabetes (13). However, neither of these studies included costs for cardiovascular outcomes, and each was based on cohort studies or literature evidence (11). A subsequent cost-effectiveness analysis based on a trial of early screening for albuminuria included patients with normal BP and cholesterol levels (14).…”
Section: Introductionmentioning
confidence: 99%
“…The impressive improvement in the eGFR should convince other government and funding agencies to implement similar approaches, because the data show that dialysis costs could be deferred as a result of slowing the progression of CKD. The substantial savings in dialysis costs from following similar strategies, including early referral, have also been highlighted in studies of adults, although substantial gaps remain in what we know about slowing this disease [22].…”
Section: Multidisciplinary Clinics For Children With Chronic Kidney Dmentioning
confidence: 99%